Axial form factor of the nucleon in the perturbative chiral quark model; Journal of Physics G: Nuclear and Particle Physics; Vol. 30, iss. 6 - Khosonthongkee K.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Gutsche Th.; Faessler A. Amand; Pumsa-ard K.; Cheedket S.; Yan Y. (2004, 2004)
Title screen